Developmental exposure to low doses of dichlorodiphenyltrichloroethane disrupts functional and morphologic maturation of the spleen in prepubertal rats - Bella B. Gagulaeva; Nataliya V. Yaglova; Sergey S. Obernikhin; Ekaterina P. Timokhina (Russian Open Medical Journal)
Dichlorodiphenyltrichloroethane (DDT) is a versatile persistent pollutant with endocrine disrupting properties and an alleged immune modulator. Objective — to evaluate the parameters of functional and morphological maturation of the spleen in prepubertal rats exposed to low doses of DDT. Material and Methods — From the moment of mating, during pregnancy and lactation, female rats received a solution of o,p-DDT (20 μg/L) instead of tap water. The offspring of intact rat dams were considered the control group. Male DDT-exposed and control rats were sacrificed on postnatal day 7. The spleens were surgically removed under sterile conditions. Anatomical and histological examination of the spleen, ex tempore proliferation of splenocytes, and assessment of splenic T cells and their ability to respond to the mitogen concanavalin A were assessed. Results — Rats exposed to DDT exhibited a significantly reduced proliferative response of spleen lymphocytes to the mitogen concanavalin A. However, morphological evaluation revealed no differences in spleen anatomy between control and exposed rats. Histological examination exposed accelerated development of lymphoid tissue in the spleen of rats exposed to DDT. The ex-tempore proliferation test yielded a higher rate of mitotic division of splenocytes in exposed rats. In contrast to controls, they had a lower percentage of T cells in their spleen. Conclusion — Developmental exposure to low doses of the endocrine disruptor DDT impairs functional and morphological maturation of the spleen in prepubertal rats. DDT accelerates the formation of lymphoid compartments and weakens the functional maturation of the spleen as the organ with an immune function.